Delivering Enduring Benefits from a Gas Development: Governance and Planning Challenges in Remote Western Australia - McKenzie, Fiona Haslam (Routledge, 2013)
This paper reviews the complex and multifaceted adjustment pressures being experienced by Onslow, a small, remote town in Western Australia's Pilbara, as a result of a large gas development. Some members of the community are enthusiastic about the opportunities that the gas industry will bring, although the majority are wary of the negative impacts of rapid growth and corporate dominance observed in other Pilbara towns during the mining boom. The paper reports on the strategies being utilised by the company, the different spheres of government and the local community representatives in order to come to an agreement about how to achieve enduring community value so that the aesthetic attributes of the town and quality of life in Onslow will be enhanced, while also accommodating a large constructive workforce which will leave within a short time (4 years). Using data collected about the Pilbara and the socio-economic impacts of the mining industry on other towns, the lessons learned from rapid growth elsewhere were applied in Onslow and the outcomes assessed and reported. It is evident that the community engagement strategies and the collaborative planning processes have been undermined by disconnects between commercial imperatives, governance frameworks, investment risk and timeframes.